2009
DOI: 10.1177/1470320309344151
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin-converting enzyme gene promoter single nucleotide polymorphisms and haplotype with major depression in a northeastern Thai population

Abstract: In the present investigation, an association between the -240A allele and a reduced risk for MDD was observed, but the genotype distributions of controls were only just in marginal agreement with Hardy-Weinberg equilibrium.The T-T haplotype in the ACE gene was significantly associated with an increased risk for MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Regarding a point of concern, the observed difference in age between the two groups in the present study may have influenced the outcome in the association test as previously discussed (Angunsri et al, 2009). Nevertheless, it is unlikely that such an age difference could significantly alter the result of this study.…”
Section: Discussionmentioning
confidence: 69%
“…Regarding a point of concern, the observed difference in age between the two groups in the present study may have influenced the outcome in the association test as previously discussed (Angunsri et al, 2009). Nevertheless, it is unlikely that such an age difference could significantly alter the result of this study.…”
Section: Discussionmentioning
confidence: 69%
“…ACE, membrane-bound endopeptidase, is expressed in many tissues including brain 13 . It is reported that ACE in neuroepithelial cells degrades neurotransmitters such as substance P, which has a role in depression 14 and that angiotensin II interacts with dopamine in some specific parts of brain 15 . Angiotensin II, acting as a stimulator of proinflammatory cytokines, makes changes on the hypothalamic-pituitary-adrenal (HPA) axis activation that develops in response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 Only one study involving Thai adults replicated the association between rs4291 and major depression. 13 Another two found no significant associations 14, 15 and another reported inverse associations with closely linked SNPs. 16 …”
Section: Introductionmentioning
confidence: 96%